2016
DOI: 10.3389/fpls.2016.00335
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptome Profiling Reveals Long Noncoding RNA Expression and Alternative Splicing Regulation during Fruit Development and Ripening in Kiwifruit (Actinidia chinensis)

Abstract: Genomic and transcriptomic data on kiwifruit (Actinidia chinensis) in public databases are very limited despite its nutritional and economic value. Previously, we have constructed and sequenced nine fruit RNA-Seq libraries of A. chinensis “Hongyang” at immature, mature, and postharvest ripening stages of fruit development, and generated over 66.2 million paired-end and 24.4 million single-end reads. From this dataset, here we have identified 7051 long noncoding RNAs (lncRNAs), 29,327 alternative splicing (AS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 76 publications
7
42
0
Order By: Relevance
“…A significant number of transcripts (26 784) were identified as lncRNAs in rose‐scented geranium. The number of lncRNAs detected in this study was comparable with the previous studies on T. aestivum (44 698 lncRNAs) , maize (20 163 lncRNAs) , Populus trichocarpa (2542 lncRNAs) , Arabidopsis (6480 lncRNAs) , rice (2224 lncRNAs) , sea buckthorn (3428 lncRNAs) , Actinidia chinensis (7051 lncRNAs) , tomato (3558 lncRNAs) , Cajanus cajan (3919 lncRNAs) , and Vitis vinifera (3210 lncRNAs) etc. However, out of the total lncRNAs detected in rose‐scented geranium, only 1.8% could be annotated against the different public lncRNA databases, as high‐confidence lncRNAs.…”
Section: Discussionsupporting
confidence: 89%
“…A significant number of transcripts (26 784) were identified as lncRNAs in rose‐scented geranium. The number of lncRNAs detected in this study was comparable with the previous studies on T. aestivum (44 698 lncRNAs) , maize (20 163 lncRNAs) , Populus trichocarpa (2542 lncRNAs) , Arabidopsis (6480 lncRNAs) , rice (2224 lncRNAs) , sea buckthorn (3428 lncRNAs) , Actinidia chinensis (7051 lncRNAs) , tomato (3558 lncRNAs) , Cajanus cajan (3919 lncRNAs) , and Vitis vinifera (3210 lncRNAs) etc. However, out of the total lncRNAs detected in rose‐scented geranium, only 1.8% could be annotated against the different public lncRNA databases, as high‐confidence lncRNAs.…”
Section: Discussionsupporting
confidence: 89%
“…Previous analyses indicated the Acc03242 / Ach03g045741 from the genome of kiwifruit ‘Hongyang’ (Huang et al ., ; Yue et al ., ; Pilkington et al ., ) encodes a WD40 protein that is highly homologous to Arabidopsis TTG1, a well‐characterized WD40 protein involved in anthocyanin metabolism (Walker et al ., ). This WD40 homolog from kiwifruit was previously shown to be expressed constitutively throughout fruit development (Tang et al ., ). Here we additionally demonstrated that there was no significant difference in expression levels of Acc03242 / Ach03g045741 between inner and outer pericarp using qRT‐PCR analysis (Figure S19).…”
Section: Discussionmentioning
confidence: 97%
“…A rapidly increasing number of lncRNAs have been identified in plants and associated with various biological processes, including fruit ripening (Tang et al ., ; Li et al ., ), reproduction (Zhang et al ., ,b; Huang et al ., ), disease resistance (Zhang et al ., ), stress responses (Qin et al ., ), photomorphogenesis (Wang et al ., ) and phosphate homeostasis (Franco‐Zorrilla et al ., ).…”
Section: Discussionmentioning
confidence: 99%